Fruit juice sonication: Implications on food safety and physicochemical and nutritional properties - Zinoviadou, Kyriaki G.; Galanakis, Charis M.; Brnčić, Mladen; Grimi, Nabil; Boussetta, Nadia; Mota, Maria J.; Saraiva, Jorge A.; Patras, Ankit; Tiwari, Brijesh; Barba, Francisco J. (Food research international, 2015)
Over the last years, consumers are increasingly demanding for nutritious, healthy and fresh-like food products, with high organoleptic quality. Nowadays, emerging non-thermal technologies have raised great interest as a viable alternative to the conventional thermal methods, since they have minimal impact on sensorial and nutritional properties of fresh foods. Ultrasound (US) is one of these promising non-conventional processing technologies and it is especially suitable for preservation of fluid foods. US may be used alone or in combination with other preservation techniques, such as mild heat temperatures, high pressures and antimicrobials. Besides, data on inactivation of food microorganisms by US alone are scarce, because the effects of US are usually not severe enough for a sufficient lethal effect. Since many studies on this subject have been published in the last two decades, this review intends to analyze the main effects of US on microbiological, nutritional and physicochemical parameters of fluid foods. While some general trends can be observed, the effects of US are usually highly variable, not only according to treatment duration and intensity, but also according to the food matrix, suggesting that each matrix should be studied and evaluated separately. Generally, the impact of US on food matrices is minimal, unless longer treatment times and higher amplitudes are applied. Other parameters such as the specific resistance of the microbial strain play also a role. •The impact of US on physicochemical and nutritional properties is minimal.•Longer treatment times and higher amplitudes induce partial loss.•US effects depend on the specific resistance of the microbial strain and the food matrix.•US combined with other technologies may be a useful tool to preserve liquid foods.•Conditions of US treatment must be optimized for each product separately.